Complete Business Statistics - Aczel, Amir D (McGraw-Hill, 2009)
Traditionally, Complete Business Statistics, 5/e has been praised for its quality of presentation and the richness of problem sets that are realistic, stimulating and challenging. The new edition will continue to provide students with a solid understanding of statistical concepts and rich problems to stimulate learning. In addition students will be exposed to the most current uses of technology in business statistics. Students and instructors alike will enjoy using this text that now has more Excel and other software applications integrated than ever before.